THE IMPORTANCE OF ECOLOGY IN THE PROCESSING OF THE FURINDUSTRY IN UZBEKISTAN - Urinova Olima Togaevna; Shamsiddinova Latofat Samariddinovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The world's ecology is doing a lot of damage these days. The protection of the environment, ecological systems, natural complexes and individual objects, improvement of the ecological situation is one of the important issues of the day. In solving ecological problems, it is necessary to carry out state ecological control, protect the atmosphere in order to comply with the legislation on the protection and use of land, soil, water, forests, natural boundaries, plants and animals. Harmonization of ecology and environmental protection, ensuring intergovernmental cooperation in the formulation and implementation of a single environmental resource management policy is one of the most important issues, and the protection of animals and the wise use of them are important components of environmental protection measures. In Uzbekistan, the cattle industry is a major contributor to the development of the country's economy.